Brief Research Report: Agreement Between Teacher and Student Reports on Students’ Acceptance and Rejection - Schoop-Kasteler, Noemi; Müller, Christoph M. (Frontiers in Education, 2021)
Student-reported peer nominations are typically used to obtain information on the social status (i.e., acceptance and rejection) of students in their classrooms. However, under certain circumstances this assessment method cannot be used, for example for logistical reasons or with students with intellectual disabilities (ID) who are not always able to fill out peer nominations. In such instances, teacher reports on students’ expected nominations may serve as a proxy. As part of a larger study on students with ID, we evaluated the agreement between teachers’ and students’ peer reports regarding individual students’ acceptance and rejection using unlimited nomination procedures in Grades 4–6 mainstream classrooms. As many students with ID cannot fill out peer nominations, this evaluation study used a sample of typically developing students without ID. Teachers (n = 27, Mage = 34.24 years, SD = 10.85; 85.2% female) nominated all peers from the classroom who they believed individual students would report as “liked” and “not liked”. For direct comparison, students (n = 441, Mage = 11.36 years, SD = 0.89; 46.8% female) themselves were also asked to report their “liked” and “not liked” nominations. Students received both more “liked” and more “not liked” nominations from their peers than from their teachers. Students’ social status as calculated from teacher reports showed only partial agreement with social status as calculated from student reports, suggesting that in mainstream classrooms student reports cannot be easily replaced by teacher reports. Perspectives on the application of teacher-reported peer nominations in special needs settings are discussed.